White wine, sparkling white wine and black caviar – The sensory experience of pairing of flavours - K. Wendin; B. Collin; S. Forsberg; H. Scander; R. Albin; F. Åhrberg; T. Ranta (International Journal of Gastronomy and Food Science, 2026)

Impact of river discharge and suspended sediments on phytoplankton in the nearshore waters of the Indian southwest coast - S. Santhi Krishnan; R. Jyothibabu; K.J. Albin; K.T. Alok; C. Karnan; R. Sajeev; S. Pratik (Marine Environmental Research, 2025)

Impact of river discharge and suspended sediments on the nearshore benthic environment along the Indian southwest coast - S. Santhikrishnan; R. Jyothibabu; R. Sajeev; C. B Vishnu; K.J. Albin; K.T. Alok; R.S. Pandiya Rajan (Science of The Total Environment, 2024)

Effects of seasons and successive upwelling phases on phytoplankton size classes in the Southeast Arabian Sea - Albin K.J; Jyothibabu R; Alok K.T; Santhi Krishnan S; Sherin C.K; Gupta G.V.M (Marine Environmental Research, 2024)

Novel green synthesis of Value-Added graphene quantum dots from bagasse and pith for biological applications - K.M. Mohamed; Albin John P Paul Winston; K. Akash; P. Sagayaraj; S. Rajeshkumar; R. Ravindhran; S. Amala Jayanthi; J. Judith Vijaya (Biocatalysis and Agricultural Biotechnology, 2024)

Factors regulating proliferation and co-occurrence of loricate ciliates in the microzooplankton community from the eastern Arabian Sea - C. R. Asha Devi; Jhimli Mondal; N. N. S. Vishnu; C. K. Sherin; K. J. Albin; I. Anandavelu; G. V. M. Gupta (Aquatic Sciences, 2024)

Optimizing Brackishwater Shrimp Farming with IoT-Enabled Water Quality Monitoring and Decision Support System - Nila Rekha P; Nishan Raja R; Albin Sunny; Soumyabrata Sarkar; Nedun R (Thalassas: An International Journal of Marine Sciences, 2024)

Winter phytoplankton size classes in the Northeastern Arabian Sea based on in-situ and remote sensing methods - K.J. Albin; R. Jyothibabu; S. Santhi Krishnan; K.T. Alok; C.K. Sherin; G.V.M. Gupta (Marine Environmental Research, 2023)

Flood-associated hydrobiological changes in the nearshore off Kochi, along the southwest coast of India - K.J. Albin; R. Jyothibabu; S. Santhi Krishnan; S. Sarath; K.T. Alok; G.V.M. Gupta (Continental Shelf Research, 2023)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Microbial Volatile Organic Compounds from Tempered and Incubated Grain Mediate Attraction by a Primary but Not Secondary Stored Product Insect Pest in Wheat - Taylor Van Winkle; Marco Ponce; Hannah Quellhorst; Alexander Bruce; Chloe E. Albin; Tania N. Kim; Kun Yan Zhu; William R. Morrison (Journal of Chemical Ecology, 2022)
There has been a dearth of research elucidating the behavioral effect of microbially-produced volatile organic compounds on insects in postharvest agriculture. Demonstrating attraction to MVOC’s by stored product insects would provide an additional source of unique behaviorally-relevant stimuli to protect postharvest commodities at food facilities. Here, we assessed the behavioral response of a primary ( Rhyzopertha dominica ) and secondary ( Tribolium castaneum ) grain pest to bouquets of volatiles produced by whole wheat that were untempered, or tempered to 12%, 15%, or 19% grain moisture and incubated for 9, 18, or 27 days. We hypothesized that MVOC’s may be more important for the secondary feeder because they signal that otherwise unusable, intact grains have become susceptible by weakening of the bran. However, contrary to our expectations, we found that the primary feeder, R. dominica , but not T. castaneum was attracted to MVOC’s in a wind tunnel experiment, and in a release-recapture assay using commercial traps baited with grain treatments. Increasing grain moisture resulted in elevated grain damage detected by near-infrared spectroscopy and resulted in small but significant differences in the blend of volatiles emitted by treatments detected by gas chromatography coupled with mass spectrometry (GC–MS). In sequencing the microbial community on the grain, we found a diversity of fungi, suggesting that an assemblage was responsible for emissions. We conclude that R. dominica is attracted to a broader suite of MVOC’s than T. castaneum , and that our work highlights the importance of understanding insect-microbe interactions in the postharvest agricultural supply chain.

Coccolithophores: an environmentally significant and understudied phytoplankton group in the Indian Ocean - M. Arundhathy; R. Jyothibabu; S. Santhikrishnan; K. J. Albin; S. Parthasarathi; C. P. Rashid (Environmental Monitoring and Assessment, 2021)

Impact of salinity on the grazing rate of a cladocera (Latonopsis australis) in a large tropical estuarine system - N. Arunpandi; R. Jyothibabu; L. Jagadeesan; K. J. Albin; K. M. M. Savitha; S. Parthasarathi (Environmental Monitoring and Assessment, 2020)

Mild steel welding is associated with alterations in circulating levels of cancer-related proteins - Anda R. Gliga; Tahir Taj; Maria Hedmer; Eva Assarsson; Lars Rylander; Maria Albin; Karin Broberg (Archives of Toxicology, 2019)
Welding fumes were recently classified as carcinogenic to humans and worldwide millions work as welders or perform welding operations. The purpose of this study was to identify new biomarkers of welding-induced carcinogenesis. We evaluated a panel of 91 putative cancer-related proteins in serum in a cohort of welders working with mild steel ( n = 77) and controls ( n = 94) from southern Sweden sampled on two occasions 6-year apart using a longitudinal analysis (linear mixed models). The significant results from the longitudinal analysis were tested for reproducibility in welders ( n = 88) and controls ( n = 69) sampled once during the same sampling period as timepoint 1 or timepoint 2 (linear regression models), i.e., in a cross-sectional setting. The models were adjusted for age, body-mass index, and use of snus. All study participants were non-smokers at recruitment. Exposure to welding fumes was assessed using questionnaires and respirable dust measurement in the breathing zone that was adjusted for personal respiratory protection equipment. The median respirable dust in welders was 0.7 (0.2–4.2) and 0.5 (0.1–1.9) mg/m 3 at the first and second timepoints, respectively. We identified 14 cancer-related proteins that were differentially expressed in welders versus controls in the longitudinal analysis, out of which three were also differentially expressed in the cross-sectional analysis (cross-sectional group). Namely, syndecan 1 (SDC1), folate receptor 1 (FOLR1), and secreted protein acidic and cysteine rich (SPARC) were downregulated, in welders compared with controls. In addition, FOLR1 was negatively associated with years welding. Disease and function analysis indicated that the top proteins are related to lung cancer as well as cell invasion and migration. Our study indicates that moderate exposure to welding fumes is associated with changes in circulating levels of putative cancer-related proteins, out of which FOLR1 showed a clear dose–response relationship. It is, however, unclear to which extent these changes are adaptive or potential early biomarkers of cancer.

Biodiversity effects of the predation gauntlet - Adrian C. Stier; Christopher D. Stallings; Jameal F. Samhouri; Mark A. Albins; Glenn R. Almany (Coral Reefs, 2017)

Death by Caffeine: Presumptive Malicious Poisoning of a Dog by Incorporation in Ground Meat - S. N. Tawde; B. Puschner; T. Albin; S. Stump; R. H. Poppenga (Journal of Medical Toxicology, 2012)

High volume of endurance training impairs adaptations to 12 weeks of strength training in well-trained endurance athletes - Bent R. Rønnestad; Ernst Albin Hansen; Truls Raastad (European Journal of Applied Physiology, 2012)

In-season strength maintenance training increases well-trained cyclists’ performance - Bent R. Rønnestad; Ernst Albin Hansen; Truls Raastad (European Journal of Applied Physiology, 2010)

Effect of heavy strength training on thigh muscle cross-sectional area, performance determinants, and performance in well-trained cyclists - Bent R. Rønnestad; Ernst Albin Hansen; Truls Raastad (European Journal of Applied Physiology, 2010)